Ocular blastomycosis in a dog - Cecco, Bianca S. de; Carossino, Mariano; Camacho-Luna, Pilar; Alling, Christopher; Carter, Renee; Elliott, Jacqueline E.; Piero, Fabio Del; Langohr, Ingeborg M. (Brazilian Journal of Veterinary Pathology, 2021)
A 2-year-old, female Poodle dog presented to the Emergency Service at the Veterinary Teaching Hospital (VTH), Louisiana State University School of Veterinary Medicine with a history of lethargy and anorexia. At clinical examination the dog was anemic and febrile. The dog was bilaterally blind. The right eye was buphthalmic and the intraocular pressure was elevated (42 mm Hg). During an ophthalmological consult, bilateral severe panuveitis and optic neuritis with secondary glaucoma in the right eye was diagnosed and treatment was instituted. Despite treatment, the intraocular pressure kept increasing (up to 72 mm Hg overnight), and the clinicians decided to enucleate the right eye due to poor prognosis. After one month, and no response to treatment, the left eye was also enucleated.